Initial experience with SOFIA as an intermediate catheter in mechanical thrombectomy for acute ischemic stroke. (27th October 2016) - Wong, Johnny H Y; Do, Huy M; Telischak, Nicholas A; Moraff, Adrienne M; Dodd, Robert L; Marks, Michael P; Ingle, Shreya M; Heit, Jeremy J
Abstract : Background: The benefits of mechanical thrombectomy for emergent large vessel occlusion (ELVO) have been established. Combined mechanical/aspiration (Solumbra) and a direct aspiration as a first pass technique (ADAPT) are valid procedures requiring an intermediate catheter for clot suction. Recently, SOFIA (Soft torqueable catheter Optimized For Intracranial Access) was developed as a single lumen flexible catheter with coil and braid reinforcement, but its suitability for mechanical thrombectomy had not been evaluated. Objective: To describe our initial experience with SOFIA in acute stroke intervention and evaluate its efficacy and safety. Methods: All patients with ELVO undergoing endovascular stroke intervention with SOFIA were identified. Demographic, presentation, treatment, and complication data were recorded. Primary outcome was Thrombolysis in Cerebral Infarction (TICI) 2b/3 revascularization rate and the number of passes required. Secondary outcomes included complication rates and discharge National Institute of Health Stroke Scale (NIHSS) score. Results: 33 patients with a mean age of 72 years were treated for ELVO with SOFIA and IV tissue plasminogen activator was administered in 67%. Vessel occlusion involved the internal carotid artery (15.2%), M1 (48.5%), and M2 (24.2%) segments, and posterior circulation (12.1%). Median presentation NIHSS score was 14 (IQR 11–19) and discharge NIHSS 4 (IQR 2–14). The Solumbra technique represented 94% of treatments and ADAPT 3%. The TICI 2b/3 revascularization rate was 94%, including 48.5% TICI 3 with an average of 1.6 passes. The symptomatic reperfusion hemorrhage rate was 6%. Procedural complications occurred in four patients, but were unrelated to SOFIA. Mortality was 21%, secondary to failed revascularization, hemorrhagic transformation, and baseline medical condition. Conclusions: Mechanical and aspiration thrombectomy with SOFIA is safe and effective with high revascularization rates. Its trackability, stability, and luminal size make SOFIA suitable for stroke intervention.